SARS-CoV-2: Information and impacts (Research, Society and Development, 2021)
In Wuhan, China, at the end of 2019 there was an outbreak of viral pneumonia of unknown cause, until on January 7, 2020, the etiologic agent of this disease was identified by the Chinese Center for Disease Control and Prevention (CDC) in that it was a Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) known as coronavirus 19 (COVID-19). Until June 1, 2021, this virus has infected around 170,814,464 people, causing 3,551,884 people to die, in addition to generating a series of social and economic problems in the world. Thus, this study aimed to document information regarding SARS-CoV-2 contained in the scientific literature, as well as the impacts generated on society by the new coronavirus. Searches were performed in the following databases: PubMed/MEDLINE, SciELO, and BVS using a search filter for articles from December 2019 to May 2021, which are the months that comprise studies related to SARS-CoV-2. Bibliographic searches were performed in May 2021 using the descriptors "COVID-19 and Impacts", "COVID-19 and Information", "Complication and COVID-19", and "COVID-19 and Fake News". Only findings in the English language (American and British) were taken into consideration. Thus, we hope that this study reinforces readers' knowledge with information about COVID-19 and its impacts on society. It also aims to measure and identify the vast scientific material that we already have available in the literature.